Katekisasi Di Tengah Dinamika Sosial-Budaya - Ransulangi, Iren; Mosey, Juliana; Gobel, Micha; Djabar, Evelin; Tumbelaka, Ananda; Sinanu, Stevania; Kahard, Theresa (PT. Giat Konseling Nusantara, 2025)
Catechesis is an important process in fostering Christian faith, especially for the younger generation. However, challenges of the times such as digitalization and shifting social values require the church to modernize the approach to catechesis. This article examines how the church can contextualize teaching materials by integrating five approaches from Christian education experts: Thomas Groome's Shared Christian Praxis method, John Westerhoff's Community of Faith Model, Jack Seymour's transformative approach, Maria Harris' holistic curriculum, and Howard Gardner's Multiple Intelligences theory. This study uses a qualitative literature study approach. The results of the study indicate that the strategy for modernizing catechesis must include the use of digital media, community-based learning, local cultural contextualization, and participatory and adaptive methods for multiple intelligences. With this approach, catechesis can remain faithful to the tradition of Christian faith but be relevant and effective in responding to the needs of today's young generation. Katekisasi merupakan proses penting dalam membina iman Kristen, khususnya bagi generasi muda. Namun, tantangan zaman seperti digitalisasi dan pergeseran nilai sosial menuntut gereja untuk memodernisasi pendekatan katekisasi. Artikel ini mengkaji bagaimana gereja dapat mengontekstualisasikan materi ajaran dengan mengintegrasikan lima pendekatan ahli pendidikan Kristen: metode Shared Christian Praxis dari Thomas Groome, Community of Faith Model dari John Westerhoff, pendekatan transformatif Jack Seymour, kurikulum holistik Maria Harris, dan teori Multiple Intelligences dari Howard Gardner. Penelitian ini menggunakan pendekatan kualitatif studi pustaka. Hasil kajian menunjukkan bahwa strategi modernisasi katekisasi harus mencakup pemanfaatan media digital, pembelajaran berbasis komunitas, kontekstualisasi budaya lokal, serta metode partisipatif dan adaptif terhadap kecerdasan majemuk. Dengan pendekatan ini, katekisasi dapat tetap setia pada tradisi iman Kristen namun relevan dan efektif menjawab kebutuhan generasi muda masa kini.